1997
DOI: 10.1046/j.1365-2710.1997.10475104.x
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: stability of morphine injected without preservative, delivered with a disposable infusion device

Abstract: Morphine hydrochloride solutions stored in disposable infusion devices degraded very slowly, particularly when preserved with sodium metabisulphite. The solutions are stable over 5 days, the maximum period of storage normally required when using disposable infusers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Mixing drugs will prevent multiple perfusions. The stability of single drugs has also been reported by numerous authors (3)(4)(5)(19)(20)(21). Most of the stability studies have been carried out on binary drug mixtures (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Mixing drugs will prevent multiple perfusions. The stability of single drugs has also been reported by numerous authors (3)(4)(5)(19)(20)(21). Most of the stability studies have been carried out on binary drug mixtures (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 86%
“…Many researchers have studied the stability of morphine solutions under different conditions of conservation (3)(4)(5). It has been found that the decomposition of morphine is accelerated in alkaline pH (3) and depends on the presence of oxygen (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the morphine used in both clinical practice and for clinical investigations contains sodium bisulfite as a preservative [8]. Until the mid 1980's sulfite preservatives were generally considered universally safe; however, their status was changed after the receipt by the FDA of more than 250 reports of serious and life-threatening reactions related to sulfite exposure through both diet and therapeutic agents [9,10].…”
Section: Introductionmentioning
confidence: 99%